A Case of Orbital Langerhans Cell Histiocytosis in an Adult - Inês Carneiro; António Friande; Maria Araújo (Acta Médica Portuguesa, 2019)
Langerhans cell histiocytosis remains an enigmatic disease with a very heterogeneous presentation. We describe a rare case of orbital Langerhans cell histiocytosis in a 39-year-old female patient who presented right orbital pain and edema of the upper right eyelid. Surgery showed a friable lesion and underlying bone irregularity. Morphological aspects and immunohistochemical profile favored the diagnosis of Langerhans cell histiocytosis, which was confirmed with evidence of Langerin expression. The staging tests did not reveal any organ involvement, so we decided to follow the algorithm proposed by Euro Histio Net: in case of unifocal disease and in a single organ, clinical surveillance was preferred. This case aims to raise awareness of a manifestation of Langerhans cell histiocytosis, which should always be considered as a differential diagnosis in adults with osteolytic orbital lesions.